A long non-coding RNA lncRNA-PE promotes invasion and epithelial–mesenchymal transition in hepatocellular carcinoma through the miR-200a/b-ZEB1 pathway. Issue 5 (May 2017) - Shen, Yuan; Liu, Shanshan; Yuan, Hanyu; Ying, Xiaomin; Fu, Hanjiang; Zheng, Xiaofei
Long non-coding RNAs have been revealed to play important roles in the progression of hepatocellular carcinoma. However, the detailed mechanisms underlying their activities are not fully understood. Using microarray technology, a number of long non-coding RNAs were previously identified to be aberrantly expressed in hepatocellular carcinoma. In this study, one of these long non-coding RNAs, designated lncRNA-PE (lncRNA promotes epithelial–mesenchymal transition), was further explored to study its expression profile and function. A cohort of human hepatocellular carcinoma tissue samples combined with benign controls and established human hepatocellular carcinoma cell lines were examined for the expression of lncRNA-PE. The biological functions of lncRNA-PE were examined by wound-healing and Transwell assays, which revealed that lncRNA-PE promotes cell invasion and migration. By detecting the level of epithelial–mesenchymal transition markers, lncRNA-PE was revealed to promote epithelial–mesenchymal transition in hepatocellular carcinoma cells. Further study suggested that lncRNA-PE downregulated miR-200a/b by repressing the primary transcript expression, enhanced ZEB1 expression, and promoted epithelial–mesenchymal transition of hepatocellular carcinoma cells. All these data imply that lncRNA-PE might play an important role in hepatocellular carcinoma development via the miR-200a/b-ZEB1 pathway.